OECD Review of Gender Equality in Colombia (OECD Publishing, 2023)
In recent decades, Colombia has pursued a strategy to encourage gender equality as an important enabler of inclusive growth and national well-being and to promote gender mainstreaming through institutions, policies and tools. This report assesses four main pillars of Colombia's governance for gender equality, analysing strengths and identifying areas for further improvement. It examines strategic planning for gender equality policy, a whole-of-government approach to promoting gender equality policy, using government tools to achieve gender equality objectives, and an inclusive and gender-sensitive emergency preparedness framework. The report also provides examples of different approaches in OECD Member and Partner countries to closing gender equality gaps. Based on this analysis, the report proposes solutions to help Colombia strengthen gender mainstreaming and gender-sensitive policy making to promote sustainable, inclusive economic growth